Network Motifs in Football - Necmi Gürsakal; Fırat Melih Yılmaz; Halil Orbay Çobanoğlu; Sandy Çağlıyor (Türk Spor ve Egzersiz Dergisi)
Complex networks often display network motifs and these can be described as subgraphs. Methods for analyzing complex networks promise to be of great benefit to almost all scientific disciplines including sports. In football if we want to disrupt the opponent's game format, we must first be aware of the pass motifs that the team often uses. Determining how to break these motifs will make an important contribution to the success of a team. In this study, 3-nodes and 4-nodes pass motifs of the teams were examined within the frame of a data set of ten games and the most frequent repetitions of these motifs were determined. In addition, we suggest that in a match, the balance can be measured by the correlation between the frequencies of the motif types and there may be an inverse relationship between this correlation and the difference in the goals of the match.